A new atypical form of lipoid necrobiosis not associated with diabetes mellitus. Clinical case and a brief review of the literature - Daniil I. Cheboksarov; Kristina J. Molodykh; Konstantin N. Monakhov; Evgeny V. Sokolovskiy (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
The article presents a description of a clinical case of necrobiosis lipoidica complicated by ulcera-tion in a 55-year-old woman and a brief review of the literature on the topic of modern ideas about necrobiosis lipoidica. The disease manifested itself in 2005 after traumatization of the upper third of both shins as a result of a fall. The patient did visit a dermatologist office for medical help, there was a slow progression of the disease. In 2017, as a result of visiting a dermatologist office at her place of residence, she was diagnosed with necrobiosis lipoidica. The ongoing therapy with vasodi-lators and topical steroids did not lead to significant improvement. In 2021, against the background of vaccination against COVID-19 (22.07.20201 and 12.08.2021 Gam-COVID-Vac Sputnik V) the patient notes a sharp deterioration of the process after the injection of the second component of the vaccine there were an increased in the area of lesion, ulceration. No data for diabetes mellitus were obtained during the examination. There is a history of a multi-nodular non-toxic goiter, for which a complete resection of the left lobe of the thyroid gland was performed in 1995 and a partial resection of the right lobe of the thyroid gland in 2003. The patient has been receiving L-Thyroxine replacement therapy since 2003. A biopsy of the affected skin was per-formed. The final diagnosis: necrobiosis lipoidica erythematous-ulcerative variant was established according to the pathoanatom-ic examination of the biopsy and atypical clinical picture. As a result of the therapy, the patient was discharged from the clinic with improvement.